Második otthonok az Alföldön - Csordás, László (Közép-Európai Közlemények, 2009)
The economic, social, technological development that has taken place in the last third of the 20th century has had significant impacts on the lives of the modern societies, touching almost all fields of life. Besides residential and work places, the places for recreation became more and more important. The most important settlements marks of this process are the boom in the number of second homes, within this category the leisure time homes and the spatial expansion of the holiday-recreation areas. The process that started from the large cities and mainly from the well-to-do layers – thus characterised as a spatial and social diffusion phenomenon – significantly changed the spatial systems of the affected settlements, their morphologies, functional division, infrastructure, land use, etc..